Improved Madden–Julian oscillation simulation using the modified moist physical parameterizations for a global climate model - Xiaohan Li; Yanluan Lin; Xiao Zhou; Yiran Peng; Xiaomeng Huang (Climate Dynamics, 2026)

A physically-refined regional climate model for the Tibetan Plateau - Kun Yang; Xu Zhou; Xiaogang Ma; Deliang Chen; Fahu Chen; Yongjiu Dai; Yaozhi Jiang; Anning Huang; Yanluan Lin; Jiarui Liu; Hui Lu; Jing Sun; et al. (Science Bulletin, 2025)

Assessing and reducing uncertainties in future mean and extreme precipitation projections over China - Ruoyan Hou; Panxi Dai; Renguang Wu; Yanluan Lin; Zhengquan Li (Atmospheric Research, 2025)

How does globally accumulated tropical cyclone energy vary in response to a changing climate? - Kaiyue Shan; Fengfei Song; Yanluan Lin; Wenchao Chu; Chengfei He; Pao-Shin Chu; Lixin Wu; Xiping Yu (Science Bulletin, 2025)

Why Super Typhoon Occurrence Over the Western North Pacific Ocean Tends to be More in Autumn Than Summer - Zhiming Feng; Xiuping Yao; Chenfei Liao; Jiali Ma; Ning Pan; Yanluan Lin (International Journal of Climatology, 2025)
Based on the tropical cyclone (TC) best‐track datasets from the China Meteorological Administration during 1949–2020 and the fifth generation ECMWF atmospheric reanalysis (ERA5) datasets, we investigate the characteristics of super typhoons (SuperTYs) over the western North Pacific (WNP) and associated mechanism in this study. The results show that SuperTYs are prone to occur in autumn over the WNP, nearly 30% of the autumn TCs develop into SuperTYs, and autumn SuperTYs account for more than half of the annual total. This is due to both favourable oceanic and atmospheric conditions. In southeastern WNP, the sea surface temperature (SST) in autumn is higher than that in summer, inducing zonal circulation anomalies and enhancing low‐level westerlies. Consequently, the monsoon trough strengthens and extends eastward, favouring enhanced autumn typhoon occurrence in the southeastern WNP. This southeastward shift facilitates TCs to remain over the warm ocean for a longer period and makes them more prone to develop into SuperTYs. Furthermore, TCs tend to take westward‐moving tracks in autumn due to stronger easterly steering flows compared with summer, resulting in more TCs passing over the South China Sea (SCS) to the east of the Philippines where the vertical wind shear (VWS) is relatively weaker and prone to develop into superTYs.

Impact of ocean mixed layer depth on tropical cyclone characteristics: a numerical investigation - Yalan Zhang; Kaifeng Han; Yuan Sun; Yanluan Lin; Panmao Zhai; Xinwen Guo; Wei Zhong (Frontiers in Marine Science, 2024)
Introduction The impact of upper-ocean temperature on tropical cyclone (TC) activity is an open issue. Compared to the attention devoted to the effect of sea-surface temperature (SST) on TC activities, much less is known about the effect of ocean mixed layer depth (OMLD) on TC activities, which is determined by the ocean temperature below the surface. Methods In this study, a series of idealized numerical experiments were conducted to investigate the possible responses of TC activities to OMLD. Results It was found that while OMLD exerts a minor influence on TC track, it evidently affects TC intensity, size, and destructiveness before reaching a certain OMLD threshold (approximately 15 m). Once the OMLD exceeds the threshold, changes in TC intensity, size, and destructiveness become marginal with further increase in OMLD. The threshold of OMLD is largely determined by TC intensity, which in turn is dictated by surface wind speed. Discussion Specifically, before reaching the threshold of OMLD, the surface wind, namely TC-related surface wind, may bring the cold water from below the OMLD, and effectively decreases the upper ocean temperature (including the SST). As OMLD increases, the effect of surface wind on SST cooling gradually decreases, leading to an increase of SST below the TC. Subsequently, the SST increase leads to more surface enthalpy flux (SEF) input into the TC by increasing air-sea temperature and moisture differences. By altering TC's thermodynamic and dynamic structures, the increase of SEF eventually results in the increase of TC intensity and size, and thus its destructiveness.

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Improved subseasonal-to-seasonal precipitation prediction of climate models with nudging approach for better initialization of Tibetan Plateau-Rocky Mountain Circumglobal wave train and land surface conditions - Yi Qin; Qi Tang; Yongkang Xue; Ye Liu; Yanluan Lin (Climate Dynamics, 2024)
Reliable subseasonal-to-seasonal (S2S) precipitation prediction is highly desired due to the great socioeconomical implications, yet it remains one of the most challenging topics in the weather/climate prediction research area. As part of the Impact of Initialized Land Temperature and Snowpack on Sub-seasonal to Seasonal Prediction (LS4P) project of the Global Energy and Water Exchanges (GEWEX) program, twenty-one climate models follow the LS4P protocol to quantify the impact of the Tibetan Plateau (TP) land surface temperature/subsurface temperature (LST/SUBT) springtime anomalies on the global summertime precipitation. We find that nudging towards reanalysis winds is crucial for climate models to generate atmosphere and land surface initial conditions close to observations, which is necessary for meaningful S2S applications. Simulations with nudged initial conditions can better capture the summer precipitation responses to the imposed TP LST/SUBT spring anomalies at hotspot regions all over the world. Further analyses show that the enhanced S2S prediction skill is largely attributable to the substantially improved initialization of the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train pattern in the atmosphere. This study highlights the important role that initial condition plays in the S2S prediction and suggests that data assimilation technique (e.g., nudging) should be adopted to initialize climate models to improve their S2S prediction.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Uptrend of the Western North Pacific Tropical Cyclone Outflow Height during 1959–2021 - Yuan Sun; Zhihao Feng; Wei Zhong; Panmao Zhai; Yanluan Lin; Shuo Lyu (Journal of Meteorological Research, 2024)

The change of Southern Hemisphere extratropical cyclone precipitation characteristics in SSP5-8.5 scenario in CMIP6 models - Dongze Xu; Dianbin Cao; Yanluan Lin (Climate Dynamics, 2023)

Impact of Revised Trigger and Closure of the Double-Plume Convective Parameterization on Precipitation Simulations over East Asia - Xiaohan Li; Yi Zhang; Yanluan Lin; Xindong Peng; Baiquan Zhou; Panmao Zhai; Jian Li (Advances in Atmospheric Sciences, 2023)

Indirect effect of diabatic heating on Mei-yu frontogenesis - Yang Hu; Yi Deng; Yanluan Lin; Zhimin Zhou; Chunguang Cui; Chao Li; Xiquan Dong (Climate Dynamics, 2022)

Impacts of Irrigation and Vegetation Growth on Summer Rainfall in the Taklimakan Desert - Dongze Xu; Yanluan Lin (Advances in Atmospheric Sciences, 2021)

A dynamical pathway bridging African biomass burning and Asian summer monsoon - Dianbin Cao; Tae-Won Park; Yongjia Song; Yuhang Wang; Zhenyu You; Yanluan Lin; Yi Deng (Climate Dynamics, 2021)

The impact of atmospheric moisture transport on winter Arctic warming: Radiation versus latent heat release - Mingju Hao; Yanluan Lin; Yong Luo; Reshmita Nath; Zongci Zhao (International Journal of Climatology, 2021)
Atmospheric moisture transport (AMT) contributes significantly to the recent accelerated Arctic warming. However, the impact of AMT has not been well quantified, not to mention the relative contribution of its impact on microphysical latent heating (LAH) and longwave radiative heating (LWH). A series of Polar‐WRF model experiments with different magnitudes of AMT are conducted to study the response of winter Arctic temperature to AMT variations. Results show that atmospheric precipitable water is very sensitive to AMT variations and thus can define the changes in surface air temperature by altering surface downward longwave radiation. Additionally, because evaporation and sublimation tend to balance the AMT‐induced moisture changes near the surface, LWH in the lower troposphere is determined by downward longwave radiation and thus can be the dominant factor for temperature variations. However, temperature in the mid‐ and upper troposphere is primarily determined by changes in LAH, because the content of ice‐phase cloud aloft is significantly affected by AMT. In addition, the changes in LWH in the mid‐ and upper troposphere are governed by upward longwave radiation, thus offsetting some of the temperature variations. These findings have implications for the attribution of Arctic current warming and the prediction of its future temperature change.

Dynamics of the spatiotemporal morphology of Mei-yu fronts: an initial survey - Yang Hu; Yi Deng; Yanluan Lin; Zhimin Zhou; Chunguang Cui; Xiquan Dong (Climate Dynamics, 2021)
Mei-yu fronts are often accompanied with prominent diabatic heating due to the development of frontal clouds and rain bands. The direct effect and relative importance of diabatic heating on the spatiotemporal morphology of Mei-yu fronts however remain unclear. Here a new frontogenesis function is derived to isolate the effect of diabatic heating and this function is then applied to the latest high resolution reanalysis product ERA5 to conduct an initial survey of dynamic and thermodynamic processes driving the intensity and structure evolutions of three typical Mei-yu fronts. It is found that the direct effect of latent heating (moisture depletion) is always frontogenetical (frontolytical) in the pre-frontal and frontal zone throughout the lifecycle of the front with latent heating (moisture depletion) in general dominates the front intensification (dissipation). Tilting is another critical process that turns the vertical gradient of equivalent potential temperature into horizontal gradient leading to frontogenesis during the front development stage, and, after the release of convective instability ahead of the front, flattens the front surface leading to frontolysis during the front decaying stage. Therefore titling maintains consistently positive contributions to the evolution of a Mei-yu front and its importance depends highly on the convective intensity near the front. The deformation effect appears frontogenetical but carries a much smaller weight compared to diabatic heating, moisture depletion and tilting. The structure evolutions of the three Mei-yu fronts studied here exhibit two distinct patterns: “bending and breaking”, and “moving and rotating”. Both patterns are dominated by the front propagation (i.e., frontogenesis through air parcels), further highlighting the critical roles played by diabatic heating, moisture depletion and titling in determining the spatiotemporal characteristics of Mei-yu fronts. As these three processes are all closely tied to updrafts, clouds and precipitation near the fronts, improved representations of clouds and convection are needed to accurately depict their feedbacks to frontal evolutions and ultimately achieve better predictions of heavy rainfall and floods associated with Mei-yu fronts.

Wet spells over the core monsoon domain of northern Pakistan during the summer season - Nabeela Sadaf; Yanluan Lin; Wenhao Dong (International Journal of Climatology, 2021)
Flooding events or wet spells have increased over Pakistan in recent years. However, a long‐term classification of large‐scale and synoptic‐scale configuration for these events has been lacking. In this study, a total of 53 wet spells during the period of 1951–2015 over the core monsoon domain of northern Pakistan are identified using rainfall data. Based on daily geopotential height fields from NCEP/NCAR re‐analysis, the dominant synoptic‐scale systems, displaying distinct low‐level circulation and moisture transport, are found during these wet spells over Pakistan. They are categorized as trough with low pressure system (LPS, 30 cases), trough without LPS (19 cases) and LPS only (4 cases) wet spells. Without the accompanying LPS over India, the trough tends to be deep and intrudes to southern Pakistan with moisture transport mainly from the Arabian Sea. In contrast, the trough is relatively shallow and interacts with presence of the LPS to steer moisture from the Bay of Bengal towards Pakistan. We found that subtropical trough is an essential ingredient of wet spells over Pakistan. This is different from wet spells over the core monsoon domain of India, which is mainly dominated by LPS. The ridge development over Siberia is a precursor to wet spells over Pakistan and provides guidance for prediction.

A new DRP-4DVar-based coupled data assimilation system for decadal predictions using a fast online localization technique - Yujun He; Bin Wang; Wenyu Huang; Shiming Xu; Yong Wang; Li Liu; Lijuan Li; Juanjuan Liu; Yongqiang Yu; Yanluan Lin; Xiaomeng Huang; Yiran Peng (Climate Dynamics, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Contribution of atmospheric moisture transport to winter Arctic warming - Mingju Hao; Yong Luo; Yanluan Lin; Zongci Zhao; Lei Wang; Jianbin Huang (International Journal of Climatology, 2019)
Atmospheric moisture transport (AMT) is known to have an influence on the winter Arctic surface air temperature (SAT). However, a systematic investigation involving a verification of the physical linkages and spatial sensitivity within the Arctic, as well as a quantification of such contribution is still lacking. Our work first verifies the variation coherence between AMT and the SAT over the winters of 1979–2015, based on multiple data sets. Climate model projections reveal tendencies towards more frequent high values in both SAT and AMT from 2010 to 2065 relative to that from 1950 to 2005, as well as a high correlation coefficient between their detrended series. Then, a composite analysis is applied based on different AMT values. During high‐AMT episodes, enhanced AMT intrudes into the Arctic, with the Norwegian Sea as the gateway, and further induces unevenly distributed warming inside the Arctic. The greatest warming occurs in the Barents‐Kara Sea, which is tightly associated with the altered atmospheric moisture content and its subsequent changes of surface radiation balance. In addition, the intruding moisture can induce latent heat release and sea ice melting, which also influences the warming. Furthermore, by conducting numerical model experiments in the winter of 2012/2013, a total warming effect of 9.66 °C averaged across the Arctic for the original AMT is revealed. By setting different incremental AMT values in five cases, the leading role of AMT is found to switch in the 0.5MT case (the case wherein the AMT value is 0.5 times the original) from altering the atmospheric moisture content to producing precipitation. This finding suggests that evenly spaced AMTs result in the alleviation of SAT increases.

Monthly variability of Luzon Strait tropical cyclone intensification over the Northern South China Sea in recent decades - Jingru Sun; Fanghua Xu; Lie-Yauw Oey; Yanluan Lin (Climate Dynamics, 2019)

Precipitable water and CAPE dependence of rainfall intensities in China - Wenhao Dong; Yanluan Lin; Jonathon S. Wright; Yuanyu Xie; Xungang Yin; Jianping Guo (Climate Dynamics, 2019)

Response of eddy activities to localized diabatic heating in Held–Suarez simulations - Yanluan Lin; Jishi Zhang; Xingrui Li; Yi Deng (Climate Dynamics, 2018)

A long-term tropical mesoscale convective systems dataset based on a novel objective automatic tracking algorithm - Xiaomeng Huang; Chenqi Hu; Xing Huang; Yang Chu; Yu-heng Tseng; Guang Jun Zhang; Yanluan Lin (Climate Dynamics, 2018)

Declining hailstorm frequency in China during 1961–2015 and its potential influential factors - Wenhui Zhao; Jianping Guo; Zhanyu Yao; Yuxing Yun; Shuo Jia; Weijian Wang; Pei Zhang; Hui Xu; Huan Liu; Liangshu Gao; Yanluan Lin; Mingxin Li; et al. (International Journal of Climatology, 2018)
Based on 55 years (from 1961 to 2015) of ground‐based hailstorm and atmospheric sounding observations, the climatological characteristics of hailstorms in China, along with potential influencing factors, were analysed. We found that hailstorms exhibit large spatial and temporal variability, with the peak occurring in spring in south China, and in summer in north China. The Tibetan Plateau (TTP) is a region with high hailstorm frequency. Overall, the frequency of hailstorms has decreased over the 55 years, although there was an increase from 1961 to 1985. In terms of diurnal variability, while hailstorm frequency peaks in the afternoon in most of China, it peaks during the night or early morning in southwest China. The magnitude of the peak increased during the 1960s and 1970s, and then decreased afterwards. Hailstorms are negatively correlated with daily mean temperature but are positively correlated with diurnal temperature range, convective available potential energy (CAPE) and totals–totals index. The increase of hailstorms during the period from 1961 to 1985 is mainly correlated with the increase in CAPE over the TTP region, while the decrease of hailstorms afterwards is correlated with all four convective parameters. The finding has significant implications for the potential impact of increasing greenhouse gases on climatological changes in hailstorm.

Narrowing the surface temperature range in CMIP5 simulations over the Arctic - Mingju Hao; Jianbin Huang; Yong Luo; Xin Chen; Yanluan Lin; Zongci Zhao; Ying Xu (Theoretical and Applied Climatology, 2018)